A review of the applications of ultra-high performance concrete in flat components and the associated fire-induced spalling risk - Xiaodong Cheng; Jun Xia; Theofanis Krevaikas; Luigi Di Sarno (AIMS Materials Science)
In the construction field, ultra-high performance concrete (UHPC) has drawn remarkable attention owing to its outstanding mechanical properties and durability, with increasingly extensive applications in flat components. Moreover, due to its dense microstructure, UHPC is highly susceptible to explosive spalling at elevated temperatures. In this paper, we comprehensively review the application status of UHPC in this domain, encompassing aspects such as bridge deck overlays, composite slabs, steel-concrete composite systems, joint connections, rehabilitation and strengthening, and thin-walled members. We deeply analyzed the spalling mechanisms of UHPC at high temperatures, mostly including thermal stress and vapor pressure mechanisms, and thoroughly investigated influencing factors such as permeability, heating rate, fiber and aggregate types, specimen size, cooling method, external load, and restraint. Additionally, we summarize effective methods to mitigate fire-induced spalling, such as the application of fire insulation, optimization of curing processes, incorporation of fibers or aggregates, and the utilization of thermal spalling-resistant admixtures. Despite the significant potential of UHPC in flat component applications, numerous challenges persist, including further validation of application feasibility, optimization and improvement of interface performance, in-depth elucidation of spalling mechanisms, research and exploration of new fiber materials, full consideration of the scale effect, and exploration and exploitation of innovative improvement solutions for fire resistance. Researchers should concentrate on addressing these issues to promote the broader and more efficient application of UHPC in the construction field.